Cultural capital, Islamism, and political distrust in Indonesia General Election: an ethnicity-based community engaged in Islamic Defenders Front (FPI) - Basya, Muhammad Hilali; Hamka, Hamka (Indonesian Journal of Islam and Muslim Societies, 2023)
Although there have been many studies investigating Islamist movements andtheir views concerning the relationship between Islam and politics, very rarestudies examining the ways particular ethnicity-based Islamist group invent andrevitalize their cultural capital in dealing with Islamism. Based on the case of therole of FPI (the Islamic Defenders Front) group in Jakarta rejecting the resultof Pemilu 2019 (Indonesian General Election), this study aims to investigatethe way a young Batavian community that is engaged in the FPI (a semi radicalIslamist organization) interpret their Batavian values and tradition in dealing with Islamism. This research uses a case study approach that investigates culturalcapital and its influence to a young Batavian community joining the FPI. Thisstudy relies more on in-depth interviews with the members as well as observation.Based on the fieldwork this article shows that tension in national political levelin Pemilu 2019 which polarized society had encouraged these young Batavians tobe engaged in an organization connecting them to wider Islamic groups. Insteadof Muhammadiyah or Nahdatul Ulama (NU), their cultural capital is moresupportive encouraging them to be engaged with the Islamic Defenders Front(FPI). Through this engagement in FPI and participation in political distrustrejecting the result of Pemilu 2019 they were not only involved with nationalissues, but also local issues dealing with their domination as an indigenous groupliving in an urban area.